Cross-diagnostic evaluation of minor physical anomalies in psychiatric disorders. (October 2021) - Sreeraj, Vanteemar S.; Puzhakkal, Joan C.; Holla, Bharath; Nadella, Ravi Kumar; Sheth, Sweta; Balachander, Srinivas; Ithal, Dhruva; Ali, Furkhan; Viswanath, Biju; Muralidharan, Kesavan; Venkatasubramanian, Ganesan; John, John P.; et al.
Abstract: Background: Minor physical anomalies (MPA) are markers of impaired neurodevelopment during the prenatal stage. Assessing MPA across psychiatric disorders may help understand their shared nature. In addition, MPA in family members would indicate a shared liability and endophenotype potential. We examined familial aggregation of MPA and their role as transdiagnostic and disorder-specific markers of 5 major psychiatric/neuropsychiatric conditions (schizophrenia, bipolar disorder, substance dependence, obsessive-compulsive disorder, and Alzheimer's dementia). Methods: Modified Waldrop's MPA scale was applied on 1321 individuals from 439 transdiagnostic multiplex families and 125 healthy population controls (HC). Stage of fetal development (morphogenetic/phenogenetic)- and anatomical location (craniofacial/peripheral)-based sub-scores were calculated. Familiality and endophenotypic potential of MPA were analyzed with serial negative binomial mixed-effect regression. Cross-diagnostic differences and the effect of family history density (FHD) of each diagnosis on MPA were assessed. Mixed-effects Cox models estimated the influence of MPA on age-at-onset of illness (AAO). Results: MPA were found to be heritable in families with psychiatric disorders, with a familiality of 0.52. MPA were higher in psychotic disorders after controlling for effects of sex and intrafamilial correlation. Morphogenetic variant MPA was noted to be lower in dementia in comparison to HC. FHD of schizophrenia and bipolar disorder predicted higher, and that of dementia and substance dependence predicted lower MPA. MPA brought forward the AAO [HR:1.07 (1.03–1.11)], and this was more apparent in psychotic disorders. Conclusion: MPA are transmissible in families, are specifically related to the risk of developing psychoses, and predict an earlier age at onset. Neurodevelopmentally informed classification of MPA has the potential to enhance the etiopathogenic and translational understanding of psychiatric disorders. Highlights: Minor physical anomalies are evaluated across psychiatric disorders in members of multiplex families. MPAs tend to co-aggregate in families with psychotic disorders. Higher MPA seems to be endophenotype marker specific to schizophrenia and bipolar disorders. Higher MPAs predicted younger age-at-onset of psychiatric disorders.